A model for CASE implementation : a Malaysian experience. - Selamat, Mohd Hasan; Othman, Abu Talib; Rahim, Md. Mahbubur; Khalil, Ibrahim
CASE tools are regarded as one of the potential directions to confront the software crisis. Many authors heralded CASE tools as a miracle solution for improved quality and higher productivity. However, benefits of CASE are unlikely to be realised unless a formal and rigorous transition plan is adopted by the IS department. Any CASE tool that is in the hand of unplanned and unprepared personnel, may produce negative results. Keeping this in view, the authors present a cyclic model for successful implementation of CASE into an organisation. Furthermore, the authors present the results of a CASE survey that investigate to what extent the public and private agencies in Malaysia have adopted any transition plan before commilling substantial financial resources. The results highlight that a large proportion of organisations have failed to incorporate any formal transition plan before introducing CASE tools. Such non-adherence has resulted in the rejection of CASE tools.